2021
DOI: 10.1183/16000617.0093-2021
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics as immunomodulators: a potential pharmacologic approach for ARDS treatment

Abstract: First described in the mid-1960s, acute respiratory distress syndrome (ARDS) is a life-threatening form of respiratory failure with an overall mortality rate of approximately 40%. Despite significant advances in the understanding and treatment of ARDS, no substantive pharmacologic therapy has proven to be beneficial, and current management continues to be primarily supportive. Beyond their antibacterial activity, several antibiotics such as macrolides and tetracyclines exert pleiotropic immunomodulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 150 publications
1
18
0
Order By: Relevance
“…Increased pulmonary IL-1ß concentrations associated with progressive fibrosis are found in patients with silicosis [ 28 , 29 ]. Consistent with this, previous studies revealed that IL-1β-, ASC- and NLRP-3-deficient mice were protected from pulmonary inflammation in response to inhaled silica particles [ 3 , 19 ]. Furthermore, pharmacological intervention by using anti-IL-1β antibody reduced inflammation and lung injury in silica exposed mice [ 14 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Increased pulmonary IL-1ß concentrations associated with progressive fibrosis are found in patients with silicosis [ 28 , 29 ]. Consistent with this, previous studies revealed that IL-1β-, ASC- and NLRP-3-deficient mice were protected from pulmonary inflammation in response to inhaled silica particles [ 3 , 19 ]. Furthermore, pharmacological intervention by using anti-IL-1β antibody reduced inflammation and lung injury in silica exposed mice [ 14 ].…”
Section: Discussionsupporting
confidence: 81%
“…Tetracycline and its derivatives have been evaluated in studies of inflammatory diseases where they are reported to be both safe and have immunomodulatory activity [ 8 12 ]. Several experimental and clinical studies highlighted anti-inflammatory and lung protective effects of tetracycline derivatives in inflammatory lung diseases including idiopathic pulmonary fibrosis and cystic fibrosis [ 13 19 ]. Recent evidence suggests that tetracycline limits both cytokine production of IL-1β and IL-18 as well as pyroptosis via selective inhibition of caspase-1, thereby reducing acute lung injury [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one study reported the effect of increased levels of TLR4. However, the direct reduction in the levels of IL-1β production by the effect of azithromycin has been related to the AP-1 transcription factor while NF-κB and MAPK pathways remain intact [ 35 ]. In vitro experimental data, using an LPS-stimulated RAW 264.7 macrophages model, have demonstrated that FFC reduced TNF-α and IL-6 production.…”
Section: Discussionmentioning
confidence: 99%
“…While BSRs are a useful conceptual tool for understanding therapeutic contributions to AMR, they are confounded by the observation of the differential effect of a given therapeutic depending on its pathogen context. Azithromycin, for example, exhibits an altered immunomodulatory pharmacological landscape in the presence of pathogenic bacteria compared to viruses, furthering the need to consider a dynamic host-pathogen interactome model when screening therapeutic candidates and the need to recognise the importance of repositioning as a method for expanding our understanding of drug-disease networks [ 234 ].…”
Section: Ia Developmentmentioning
confidence: 99%